IMPLEMENTASI BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KRITIS PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR:KAJIAN LITERATUR - Setianingrum, Reni Dyah Kaeksi; Haryadi; Santoso, Bernadus Wahyudi Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to systematically review research on the use of picture storybooks to enhance critical reading skills in Indonesian language learning at the elementary level. Using the Systematic Literature Review (SLR) method, this study identifies and synthesizes ten empirical articles published between 2021 and 2025, obtained from Scopus, Google Scholar, and ERIC databases. Thematic analysis was conducted to examine research trends, methods, and key findings. Results indicate that picture storybooks—both printed and digital—effectively foster students’ critical reading through the integration of text and visuals that stimulate reflection, interpretation, and social awareness. Additionally, multimodal learning through picturebooks promotes higher-order thinking by combining cognitive, emotional, and social dimensions. In conclusion, picture storybooks serve as an effective medium for developing critical literacy in Indonesian elementary education.